1974
DOI: 10.1111/j.1471-4159.1974.tb04396.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF γ‐AMINOBUTYRIC ACID ON BRAIN MITOCHONDRIAL ATP SYNTHESIS1

Abstract: —Rat brain mitochondrial ATP synthesis was studied by measuring labeled orthophosphate incorporation into ADP to form ATP. GABA stimulates ATP synthesis, and this effect requires glutamate since with GABA alone little ATP is formed. The significance of this effect by GABA is unclear, but the mechanism may relate to induction of conformational change or chelation of cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Under these conditions, we find the cortical energy charge of the adenylate pool to normalize quickly after the circulatory restoration, 22 and isolated brain mitochondria show unimpaired synthesis of ATP. 23 These results indicate that energydependent processes, rather than energy-synthesizing machinery, are particularly vulnerable to ischemia. That membrane in integrity is such a vulnerable, energy-dependent process is possible, but our data do not support a firm conclusion.…”
Section: Discussionmentioning
confidence: 85%
“…Under these conditions, we find the cortical energy charge of the adenylate pool to normalize quickly after the circulatory restoration, 22 and isolated brain mitochondria show unimpaired synthesis of ATP. 23 These results indicate that energydependent processes, rather than energy-synthesizing machinery, are particularly vulnerable to ischemia. That membrane in integrity is such a vulnerable, energy-dependent process is possible, but our data do not support a firm conclusion.…”
Section: Discussionmentioning
confidence: 85%
“…49 This would most likely affect endothelial GABA productions, especially when we have observed that GABA produced by endothelial cells regulate metabolism via fatty acid oxidation processes.…”
Section: Discussionmentioning
confidence: 99%
“…49 Therefore, we evaluated whether GABA increased the synthesis of ATP in endothelial cells and potential mechanism(s) involved. We observed that in the presence of LAG, an inhibitor of GABA synthesis, the steady-state basal levels of intracellular ATP decreased, whereas the levels of ATP increased in the presence of Gc.…”
Section: Discussionmentioning
confidence: 99%